2020
DOI: 10.3390/su12104320
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Marketing in Dental Tourism—Factor of Sustainable Development in Romania

Abstract: Dental tourism is a growing and emerging phenomenon that is becoming more attractive to patients due to its potential for decreased expenses, increased convenience, and immediacy of treatment. The necessity for travel is the primary motivation for seeking dental treatment due to the successful cooperation between tourism and healthcare. While dental tourism has been largely researched from the perspective of the patient, our research is the first research to apply a concomitant approach on dental clinics and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…Surprisingly, despite having the opportunity to become much better acquainted with all aspects of dental profession and employment prospects after graduation, only 36.8% of students said that their perception of dental tourism had changed for the better during their studies. Since 88.3% of them had a positive opinion about dental tourism, it is a good indicator of how much dental tourism is actually recognized as a profitable activity and attractive career choice in the general population of countries that are receptive markets for dental tourism, which was confirmed by previous research [19,26,27]. When it came to students' attitudes and opinions on ethi cally po-tentially problematic aspects of dental tourism, as many as 60.7% of students agreed with the statement that accelerated work procedures, reduced possibility of follow-up controls, excessive focus on profit, and questionable quality of work of some dentists and dental procedures within dental tourism can create certain moral dilemmas.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Surprisingly, despite having the opportunity to become much better acquainted with all aspects of dental profession and employment prospects after graduation, only 36.8% of students said that their perception of dental tourism had changed for the better during their studies. Since 88.3% of them had a positive opinion about dental tourism, it is a good indicator of how much dental tourism is actually recognized as a profitable activity and attractive career choice in the general population of countries that are receptive markets for dental tourism, which was confirmed by previous research [19,26,27]. When it came to students' attitudes and opinions on ethi cally po-tentially problematic aspects of dental tourism, as many as 60.7% of students agreed with the statement that accelerated work procedures, reduced possibility of follow-up controls, excessive focus on profit, and questionable quality of work of some dentists and dental procedures within dental tourism can create certain moral dilemmas.…”
Section: Discussionsupporting
confidence: 63%
“…This research, together with the statements of dental practitioners dealing with dental tourism in countries with large populations at or below the poverty line, showed that in dental profession as a whole, there is a tendency to focus on private practices and patients who can afford expensive and complicated dental procedures, which leads to a decline in the level of quality and access to healthcare for socially vulnerable patients in countries with highly developed medical and dental tourism [17,[20][21][22]. On the other hand, in future research, it would be interesting to investigate whether in the Republic of Croatia, Bosnia and Herzegovina, and the Republic of Serbia there is a trend similar to that observed in Mexico and Romania, where many young dentists are forced to look for work in dental tourism because due to excessive enrol lment quotas, there is a surplus of dentists in the labor market in relation to the actual needs of these countries [20,21,26,27].…”
Section: Discussionmentioning
confidence: 94%
“…Measures to restore travellers' confidence will play an important role in attracting tourists after crisis [47], to which the inbound marketing strategy provides a response, as it is based on contact with the future tourist through highly specialised content.…”
Section: Discussionmentioning
confidence: 99%
“…They aimed to determine the optimal number and capacity of medical and accommodation units. A study with the primary goal of providing comprehensive empirical evidence from the perspective of the dental clinics and tourism agencies in Romanian dental tourism was presented by Oltean et al (2020). The results of their study indicated that dental tourism and tourism agencies are interested in investing, promoting, and creating a partnership to create a sustainable industry of dental tourism.…”
Section: Dental Tourismmentioning
confidence: 99%